Academic Ranking of World Universities: Changes in World Higher Education? - Cheng, Ying (International Higher Education, 2015)
Academic Ranking of World Universities has been published consecutively for more than a decade so that it provides an opportunity to observe the changes of universities and countries during this period. More and more countries began to have Top 500 universities and those emerging countries are mainly from Middle East and Eastern Europe; the number of Chinese universities among Top 500 significantly increased while the number of Top 500 universities from US and Japan decreased.